Comparative Study of Parameter Estimation Methods in Pharmacokinetic Model with Oral Administration: Simulations of Theophylline Drug Concentration - Zulkarnaen, Diny (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2024)
Parameter estimation for the elimination and absorption rate constants is performed in a pharmacokinetic model, where a drug is administered orally. Some methods have been introduced to estimate these parameters but without comparison which one gives better estimates. Here, two different methods are used for comparison in estimating the absorption rate constant: the Wagner-Nelson and residual methods. The Wagner-Nelson method requiring fewer data sets while the residual method uses all available data sets for estimation. For the elimination rate constant estimate, we use only the least square error method. Simulations are conducted using sample data points of Theophylline drug concentration that varies over time to estimate the parameters. These parameter values are then utilized to approximate the drug concentration over time, using both methods. These approximations are then compared with the actual data sets to see and calculate the error values so that the best method can be determined. The comparison shows that the residual method provides better approximation since this method utilizes the entire sample data points, while the Wagner-Nelson uses only the data in the beginning time, that is when the absorption process is dominant.